Effect of Diabetes on the Male Reproductive System—A Histomorphological Study - Kotian, Sushma R.; Kumar, Ashok; Mallik, Sanchari Basu; Bhat, Nandini P.; Souza, Anne D.; Pandey, Arvind Kumar (Journal of Morphological Sciences, 2019)
Introduction Type 1 diabetes is an autoimmune disorder characterized by lack of insulin production by the β cells of the pancreas. This lack of insulin causes a variety of systemic effects on the metabolism of the body, one of which is reproductive dysfunction. The present study investigates the effects of diabetes on the male reproductive system of streptozotocin (STZ)-induced diabetic rats.Material and Methods A total of 18 adult male Wistar rats weighing ∼ between 250 and 300 g were included in the present study. The animals were divided into normal and diabetic groups. The diabetic group was further subdivided into 2 subgroups with durations of 24 and 48 days. A single dose of STZ (40 mg/kg body weight) was administrated intraperitoneally to the animals of the diabetic group. After the planned duration, the testes and epididymides were dissected, and their gross weight was measured. The tissues were then processed for histological study.Results The gross weight of the testes and epididymides in diabetic rats at 24 and 48 days showed a decrease in comparison to the control. (p < 0.01 for testes and epididymides).Diabetic animals presented a significant decrease in the diameter of the seminiferous tubules compared with the control group (p < 0.01). The epididymides in the diabetic groups showed a considerable reduction in the tubular surface area compared with the control group (p < 0.01). There was also a reduction in the mean diameter, which was measured using the maximum and minimum diameter of the tubules (p < 0.01).Conclusion The present study is an insight into the adverse effects that diabetes can have on the tissue structure of the testes, of the epididymides, and ultimately on the process of spermatogenesis.
Keywords: diabetes mellitus; testis; epididymis; streptozotocin (STZ); male infertility